"Back-stage" dissent: student Twitter use addressing instructor ideology. Issue 2 (3rd April 2018) - Linvill, Darren L.; Boatwright, Brandon C.; Grant, Will J.
ABSTRACT: In this content analysis, we explored how students address instructor ideology in the university classroom through the social media platform Twitter. We employed Boolean search operators through Salesforce Marketing Cloud Radian6 software to gather tweets and identified English language tweets by how students referenced their instructor's ideology. Tweets originated in the United States (U.S.), the United Kingdom (U.K.), and Australia. Using qualitative coding procedures, we identified seven themes in the data that described how students wrote about instructor ideology on Twitter: venting regarding instructor's ideology, sharing classroom anecdote, affirming instructor's beliefs/actions, expressing grade concern, articulating an opposing view, reporting conflict, and indicating confusion . Across categories, Twitter was employed primarily as a back-stage means to communicate expressive dissent regarding instructor ideology and also to demonstrate students' identity. We identified differences between categories based on the perceived ideology of the students' instructors as well as differences in the number of tweets per capita originating in each country.